Design examination through pattern characteristic identification: a new Kain Punca Potong (KPP) weaving design - Ahmad, Nani Hartina; Shaari, Nazlina; Mohd Ali, Noor Azizi; Abd Latif, Muhammad Pauzi (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
The weaving industry is regarded as one of the world's most popular industries. Clearly, designers' ideas gave them a drive to start a conversation about the future of design studies and research training, as well as practicing a fashion that illuminated this industry. Vigorous efforts are being exerted into producing new processes, with intensifying designing endeavors from design motifs of textile design. This paper presents a detailed study on weaving design which functions as a new approach to KPP weaving design process by defining pattern characteristics of woven fabric design. Generally speaking, there is no evidence that KPP design identity characteristics can be implemented solely on the basis of the idea process. A literature review was performed to define the current framework relevant to the choice of design and motifs and the implementation of pattern recognition characteristics for KPP in the weaving industry. It is shown that weaving design patterns and characteristics can be used as a single review point and should therefore be used as KPP's review technique for this research. When attempting to identify design innovation and motif selections in fabric weaving, a design framework for design identification through pattern characteristics is significant. The result showed that the design framework generated from this study will provide the overall aesthetic value for KPP pattern characteristics, which can serve as a new approach in weaving design and design studies, with the potential for further development suitable for future research, as suggested from the results of this study.